Continuous Sliding Mode Control of Flow-Induced Vibrations - A. Baz (Shock and Vibration)
Vortex-induced vibrations of flexible circular cylinders and galloping oscillations of square prisms are controlled using a robust continuous sliding mode (CSM) controller. The ability of the CSM controller in rejecting the flow-induced disturbances and accommodating parameter uncertainties is numerically demonstrated. In the present study, emphasis is placed on the development of theoretical models that describe the interaction between the flexible structures, the flow-induced excitation, and the CSM controller. In our development, the vortex-induced vibrations are based on the lift-oscillator model of Hartlen and Currie and the galloping phenomenon is described using Parkinson and Smith's model. The effectiveness of the CSM controller in suppressing the flow-induced vibrations of cylinders and square prisms is evaluated at various flow conditions and levels of structural uncertainties. The effect of the design parameters of the CSM controller on its performance is also investigated. The results obtained in the study suggest the potential of the robust control strategy presented as an important tool for rejecting undesirable and unmeasurable disturbances acting on critical structures that have considerably large parameter uncertainties.